PENGARUH KOMUNIKASI PERSUASIF BIDAN TERHADAP PENGAMBILAN KEPUTUSAN IBU DAN KELUARGA YANG MENGALAMI KEHAMILAN RISIKO TINGGI - Ai Nur Zannah (Jurnal Medikes (Media Informasi Kesehatan), 2020)
The coverage of management pregnancy complications in Indonesia tends to increase every year, but not yet comparable to a decrease in maternal morbidity and mortality. This was allegedly due to the increase in the number of high-risk pregnant women each year and because of the delay in referral due to delays in the mother and family in seeking care or deciding on approval of actions when there was a risk of even complications / emergencies. Delayed decision making is assumed due to lack of awareness of the mother and family due to lack of convincing and ineffective health communication carried out by health workers, especially midwives in delivering information about the risks and complications of pregnancy. Effective communication in changing behavior is persuasive communication that can be learned by midwives in order to help convince mothers, families and the community to be aware of the risks so that they can quickly and accurately make decisions for handling / action. This study aims to analyze the effectiveness of midwives' persuasive communication on the decision making of mothers and families experiencing high risk pregnancies. The design of this study uses a quasi-experimental pre-posttest with control groups. Subjects were selected based on inclusion criteria by simple random sampling for the treatment and control group, with a total of 30 midwives in the Jember Regency. Communication is measured by a checklist and decision making of pregnant women viewed from filling out the questionnaire. Data analysis with simple linear regression test to assess the effectiveness of midwife persuasive communication on decision making for pregnant women. The results showed a significant effect of persuasive communication on maternal decision making by 49% (P <0.001). Persuasive communication into an intervention increases the competence of midwives' promotives so that they can help convince mothers, families and the community to be aware of the risks, there is no delay in referrals that cause pain or even maternal death.